IMPLEMENTASI APLIKASI MOBILE CITY KUDUS UNTUK MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KABUPATEN KUDUS - Triyono, Bagas; Hadi, Krishno (Program Magister Ilmu Administrasi dan Kebijakan Publik, Pascasarjana, Universitas Pasundan, 2025)
This article was written to provide an overview of the implementation of the Kudus Mobile City application in improving the quality of public services in Kudus Regency, Central Java, Indonesia. This research was conducted using a qualitative descriptive research method, in which the data sources used were secondary data with case studies and previous literature. The results of the study show that the implementation of the Kudus Mobile City application is in accordance with the concept of public service according to applicable regulations and norms. It's just that this application still needs a lot of development in order to succeed in improving the quality of public services in Kudus Regency